Analysis of the Effect of Islamic Income Ratio (ISIR) on The Profitability of Sharia Banks in Indonesia - Nur Ahmadi Bi Rahmani; Dedy Lazuardi; Nuri Aslami (Journal of Management and Business Innovations, 2020)
The purpose of this study is to examine the impact of the Islamic Income Ratio (IsIR) on the profitability of Islamic banks in Indonesia over the five years 2012-2019. This study employs a quantitative method and draws on secondary data sources. It was decided to apply a basic linear regression methodology. The Islamic Income Ratio (IsIR) is the independent variable, and the profitability is proxied by the Return on Assets (ROA) as the dependent variable. The data processing analytic tools were SPSS 22.0. The findings revealed that a partially Islamic Income Ratio (IsIR) positively and statistically significantly impacted profitability in the study.Keywords: Islamic Income Ratio (IsIR), profitability